Marketing channels for goat meat in Turkey - Ogun S.; Koluman N.; Daskiran I. (The value chains of Mediterranean sheep and goat products. Organisation of the industry, marketing strategies, feeding and production systems, 2016)
Goat meat is a major red meat protein supplier to populations in many parts of the globe and is becoming a significant contributor to the income of livestock producers in those regions. Over 90% of the world’s goat populations are in developing countries. In Turkey, goats have traditionally been reared for subsistence farming purposes in micro and small mixed farming systems. Following a significant decline in numbers over a three-decade period, goats are now being bred in increasing numbers in many regions of Turkey. Whilst sustainable agriculture principles are being promoted in such agricultural development, with consideration to both producer and consumer needs; efforts to organize enterprising marketing channels for goat meat production in Turkey have had limited success. This paper reviews the past and present situation of goat meat production in Turkey, taking into account geographic and landscape limitations, discussing non-suitability of goat breeds being used as a by-product of the dairy goat industry for meat production and also highlighting effective supply chain collaboration to enable stakeholders to deal with complexity and potential market threats.
Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2015/06/16-18, Montpellier (France)